Cold‐adapted bacteria for bioremediation of crude oil‐contaminated soil. Issue 8 (13th October 2015) - Wang, Jingxiu; Wang, Junming; Zhang, Zhongzhi; Li, Yongfeng; Zhang, Beiyu; Zhang, Zhiyong; Zhang, Guangqing
Abstract: BACKGROUND: There are many cold climate terrestrial sites contaminated with petroleum hydrocarbons. Successful bioremediation in these regions relies heavily on suitable microorganisms with biodegrading capability at low temperatures. This work aims at screening cold‐adapted bacteria strains and examining their capability of biodegrading petroleum contaminants. RESULTS: Eleven strains of cold‐adapted bacteria were isolated from oily sludge taken from a cold environment. Three strains, identified as Chryseobacterium, Bacillus and Pseudomonas, respectively, demonstrated high efficiency in biodegradation of crude oil pollutants based on the growth curves and oil removal rate. The optimal degradation conditions of the three bacteria were 10 °C, pH 7 and salinity of 10 g L −1 for a crude oil concentration at 1000 mg L −1 . Under these conditions, the oil removal of the three bacteria after 8 days was 62.3, 61.6 and 60.9%, respectively. The strains were applied in simulated bioremediation tests using artificial contaminated soil containing 5.8–10.6 g oil kg −1 soil and achieved 61–78% oil removal after 150 days of bioremediation at 10 °C. CONCLUSION: The three cold‐adapted bacteria strains are capable of degrading crude oil efficiently at low temperatures and thus are suitable for bioremediation of petroleum contaminated soils in cold environments. © 2015 Society of Chemical Industry